Comparison of methods for the determination of biodegradable dissolved organic carbon in potable water supply: use of a novel biofilm - Zappia, L.; Alessandrino, Michael; Garbin, S.; Pringle, Paul; Heitz, Anna; Joll, Cynthia; Masters, D.; Hiller, B.; Capewell, S.; Franzmann, P.; Plumb, J.; Vitzthum von Eckstaedt, S.; et al. (International Association on Water Quality, 2008)
Potable water treatment in the state of Western Australia is challenged in many instances by the presence of high and variable levels of dissolved organic carbon (DOC), particularly in surface water supplies. In recent years the effects of climate change on local sources, in combination with the ever-present requirement for on-going disinfection effectiveness and disinfection by-product regulation has driven the need for the development of innovative, sustainable processes for the removal of DOC. Extensive pilot plant studies over a number of years have demonstrated the effectiveness of biological filtration for cost-effectively managing a variety of high DOC source waters, consequently biofiltration is seen as a process of choice for organics removal in drinking water in Western Australia. Although there are a number of indicators for measuring the efficacy of organic carbon reduction across biological treatment processes (e.g., DOC concentration, SUVA, etc), none currently are able to reliably inform on the change in the ?non-refractory? organic carbon component of DOC (i.e. biodegradable dissolved organic carbon [BDOC]) which arises from microbiological metabolic activity in the biological treatment process. Knowledge of this parameter is of critical importance to the understanding of biological stability of the finished water entering a distribution system. We have therefore investigated a number of analytical procedures in order to develop a robust test method to accurately quantify this important aspect of biofilter performance. The paper reports a comparison between conventional and rapid methods for the determination of BDOC using immobilised biofilms enriched on deep aquifer water. Effective sample collection, preparation and method of analytical analysis, method validation using natural source water with and without addition of standard amounts of assimilable organic carbon (e.g. acetate), and reproducibility of test results are discussed.